2009
DOI: 10.1136/adc.2008.149880
|View full text |Cite
|
Sign up to set email alerts
|

Protecting infants against measles in England and Wales: a review

Abstract: This study suggests that many infants being born in the UK will become susceptible to measles before 6 months and will be able to respond to vaccine between 6 and 9 months of age. It is proposed that current guidance is changed to recommend passive immunisation with human normal immunoglobulin for most infants exposed to measles below 6 months of age. For infants aged 6 months or over exposed to measles, vaccination with MMR may be given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
0
13
0
4
Order By: Relevance
“…Therefore, it is possible that some of these infants, particularly those over the age of 6 months, may be susceptible. 27 Further modelling could estimate the effect of including these infants, in addition to expanding analysis to account for age-sex and geospatial mixing patterns. 16 Although immunisation data held by CHIS are more up to date and timely than COVER data, there may be delays in the reporting of information from GP practices to CHIS; however, this is unlikely to be significant to impact on WHO susceptibility thresholds for this analysis.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…Therefore, it is possible that some of these infants, particularly those over the age of 6 months, may be susceptible. 27 Further modelling could estimate the effect of including these infants, in addition to expanding analysis to account for age-sex and geospatial mixing patterns. 16 Although immunisation data held by CHIS are more up to date and timely than COVER data, there may be delays in the reporting of information from GP practices to CHIS; however, this is unlikely to be significant to impact on WHO susceptibility thresholds for this analysis.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…The waning of maternally derived protection under current vaccination system may explain an increasing proportion of infants being susceptible to measles before the age of measles vaccination. 26,27 Accordingly, our serological data of <1 y normal infants clearly suggested that 55.9% were found to be seropositive. The rate was lower than that of in 2011 when our previous survey was carried out.…”
Section: Discussionmentioning
confidence: 90%
“…At intervals, outbreaks do occur, facilitated by a primary and secondary vaccine failure as well as limited coverage of vaccination [2,7,18,28] and waning of antibodies in adolescents and young adults, often even in individuals vaccinated with 2 doses [6]. For the moment, however, the clinical consequence of this susceptibility gap in population under 1 year old seems to be limited: most outbreaks do not involve infants below the age of 12 months.…”
Section: Discussionmentioning
confidence: 96%